ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2011) - Niztiar, Gata; Muharam, Harjum (Diponegoro Journal of Management, 2013)
Capital structure is an equalization beetwen the use of debt and the use of own capital, it means how much  own capital and how much debt that will be used can produce an optimal capital structure.This  research  aims  to  analyze  factors  which  influence  capital  structure  of  miningcompanies that listed in the Indonesia Stock Exchange. The variables studied include profitability, asset structure, sales growth, liquidity, operating leverage and difference years.Sampling method used in this research is purposive sampling. It is the sampling method based on certain criteria. The number of samples used in this research are 16 mining companies that based on the criteria. The research was conducted in the period 2008-2011. So the observationdata obtained at 64 observation data, but in normality test 13 data must be ommited, so only 51 data used as observation data. The analysis used multiple regression, which is preceded by a testconsisting of the classical assumption test for normality, heteroscedasticity test, test of multicollinearity and autocorrelation test. Hypothesis testing is using F test and t test.The results of data analysis or regression indicate that profitability, asset structure, salesgrowth, liquidity, operating leverage and difference years together influence the company's capital structure. While partially showed only profitability and liquidity significant effect on capital structure